The use of technology as an instrument to support the attention of the old persons and the possible increase of their autonomy - Gerardo, F.; Rodrigues, B.; Vasconcelos, M. João; Oliveira, T.; Silva, M.; Alves, G, (VII Congreso Red Española de Políticas Sociales: “Políticas sociales ante horizontes de incertidumbre y desigualdad”, 4 y 5 de octubre 2018, Zaragoza, 2018)
This article intends to explain the impact of a project using new technologies on older adults named Cordon Gris. This project uses information and communication technologies (ICT) while promoting the “Ageing in place” paradigm with the aim to assist older people in maintaining a healthy and independent life, as well as preventing inadequate nutrition. This paper describes the main strategies which were developed towards the acceptance, utilization, and finally, the adoption, of ICT - in particular, the Cordon Gris system. The article also gives an account of the interactive process to design the Cordon Gris prototype, and the importance of the users’ participation during those stages. We shall argue that such participation has improved technology acceptance, although support and training courses have been needed to ensure usability among older adults. The focus is here given on Portuguese users (between 63 and 87 years old) who answered questionnaires before and after the field trials. The main results showed that after 6 months of training with weekly sessions, these people’s ability to use technology passed from the basic level to advanced one. They were not only able to use the technology on their own but, what is most interesting, adopted it as something useful for their lives. We can therefore conclude that however few educational and economic resources characterized the participants, their training enabled greater social participation, increasing thus their quality of life and autonomy.